knowledge, attitude and practice on cold chain among general practitioners in kelantan - Baharuddin, Azira Haji (2012)
Knowledge, Attitude And Practice On Cold Chain Among General Practitioners In Kelantan. In Malaysia, the number of private doctors has been increasing each year. It is estimated that 20-30% of Malaysian population received immunization service from private clinics. The objectives of the study are to determine the knowledge, attitude, adherence and associated factors for optimal temperature of cold chain. Cross sectional study was conducted from April to December 2010 among general practitioners in Kelantan. The study used a self administered questionnaire, refrigerator inspection form and recording of refrigerator temperature. There were 89 general practitioners involved with response rate of 80.9%. The mean(SD) score for knowledge and attitude were 79.9%(5.43) and 68.8%(5.48) respectively. Only 14 (15.7%) of general practitioners were able to maintain optimal temperature. There were two significant associated factors for optimal temperature namely total working experience (p : 0.035) and duration of working as a general practitioner (p : 0.048). Despite high percentage of good knowledge, the majority of respondents have poor attitude on cold chain. The adherence to recommended guideline was unsatisfactory. Total working experience and duration of working as general practitioners were significant associated factors for optimal temperature.